Surface pressure transients in mesoscale convective systems - Knievel, Jason C., author (Colorado State University. Libraries, 1996)
For decades meteorologists have observed that mesoscale convective systems (MCSs) increase surface pressure beneath and immediately behind their leading cumulonimbi ( the mesohigh) and reduce surface pressure at the rear edge of their anvils (the wake low). By enhancing coarse surface pressure observations of 12 PRE-STORM MCSs, I exposed transitory highs and lows living within mesohighs and wake lows. I propose that these transients are the more elemental MCS surface pressure perturbations; mesohighs and wake lows are merely temporal and spatial envelopes of transients. Moreover, existing theories of mesohigh and wake low origins readily apply to the ephemeral transients. A quasi-Lagrangian analysis of 92 transients produced five primary results. First, as the MCSs matured, the difference between each complex's transitory highs' mean pressure and transitory lows' mean pressure increased in 78% of the conclusive cases. Second, there is no clear evidence that transitory highs consistently strengthened before their partner transitory lows. Third, transient paths reflect MCSs' occasional. symmetric-to-asymmetric metamorphoses. Fourth, composites of the time-evolution of the numbers and apparent sizes of transients partially support theories of MCS upscale evolution. Fifth, composite transient numbers and apparent sizes vary almost identically with time in a pattern that closely resembles the fluctuation of stratiform and convective volumetric rain rates of MCSs studied by McAnelly and Cotton (1992).
Spring 1996.
Also issued as author's thesis (M.S.) -- Colorado State University, 1996.
Keywords: Convection (Meteorology)